Exploring Open and Distance Learning Reform at the National University of Lesotho: A Managerial Perspective - Nketekete, Malefetsane; Mojalefa, Mamoeletsi Limakatso (International Review of Research in Open and Distributed Learning, 2021)
This study investigated how open and distance learning (ODL) reform was managed within the Institute of Extramural Studies (IEMS), at the National University of Lesotho (NUL). The reform was introduced during the 2017/18 academic year with first-year programmes in three departments: (a) Adult Education; (b) Business and Management Development; and (c) Research, Evaluation, and Media. The study employed interviews and analysis of institutional documents as data collection techniques. Interviews were held with eight programme coordinators, four department heads, and the director of IEMS. Purposive sampling was used to select the participants to the study given their strategic position in the management and implementation of the reform. Qualitative content analysis was used to interpret the data. The findings suggested that the ODL programmes were introduced without a policy and comprehensive plan. The implementation faced several challenges such as finance, as well as infrastructural and human resources. Evidence from the literature has suggested that compared to face-to-face strategy, ODL as an educational strategy requires special resources, support, and funding. Thus, curricular materials should be adapted for the ODL context, taking into account students’ characteristics. The study found that these pertinent requirements were not considered, and implementation continued as if the reform still constituted face-to-face or campus-based instruction.